Formulation and Physical Stability Test of Effervescent Tablets Containinglactobacillus Bulgariscus Probiotic Bacteria with Wet Method - david tanu jaya (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2019)
The purpose of this study was to determine whether the physical condition and stability of effervescent tablets containing probiotic bacteria differed from other effervescent tablets in the market. The bacterium used to make effervescent tablets is Lactobacillus Bulgariscus which is usually found in yogurt which usually helps the process of forming milk into yogurt. This effervescent tablet uses 3 variations of malic acid and citric acid: 0.8: 0.4; 0.4: 0.4; 0.4: 0.8. Tablets made using probiotic bacterial powders are dried using a spray dryer and using a wet granulation method to make effervescent tablets. The results showed that effervescent tablets containing probiotic bacteria had the results of each evaluation in accordance with the requirements of the 5th edition of Indonesia pharmacopoeia and the best and most stable formula was formula 1 and the formula that barely met the requirements was formula 3. In the test results stability is known that the most ideal storage temperature on effervescent tablets is at cold temperatures around 80. Because at that temperature the bacteria are in the stationary phase and the tablets are noteasy to get an acid-base reaction in the Effervescent tablets.Keywords: Probiotics, Effervescent Tablets, Stability, Lactobacillus